2021
DOI: 10.3389/fonc.2021.610637
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance-Guided Stereotactic Body Radiotherapy of Liver Tumors: Initial Clinical Experience and Patient-Reported Outcomes

Abstract: Purpose/ObjectiveStereotactic body radiation therapy (SBRT) has emerged as a valid treatment alternative for non-resectable liver metastases or hepatocellular carcinomas (HCC). Magnetic resonance (MR) guided SBRT has a high potential of further improving treatment quality, allowing for higher, tumoricidal irradiation doses whilst simultaneously sparing organs at risk. However, data on treatment outcome and patient acceptance is still limited.Material/MethodsWe performed a subgroup analysis of an ongoing prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 54 publications
(76 reference statements)
1
19
0
Order By: Relevance
“…Lastly, outcomes data linked to this dataset was unavailable. However, peer-reviewed evidence on clinical outcomes for 0.35T-MRgRT with or without oART in both prospective and retrospective series continues to grow [ 4 20 ]. Ongoing and completed prospective trials awaiting maturation of outcomes data will provide additional insights in the coming years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lastly, outcomes data linked to this dataset was unavailable. However, peer-reviewed evidence on clinical outcomes for 0.35T-MRgRT with or without oART in both prospective and retrospective series continues to grow [ 4 20 ]. Ongoing and completed prospective trials awaiting maturation of outcomes data will provide additional insights in the coming years.…”
Section: Discussionmentioning
confidence: 99%
“…Despite eight years of clinical use, MRgRT is still generally considered a novel technology, and optimal clinical applications continue to be investigated. However, a growing body of prospective and retrospectively collected data on clinical outcomes for some difficult-to-treat cancers has become available [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. While a number of users has reported on the clinical use of MRgRT, the general pattern of utilization of these systems in Europe and Asia has not been reported [21][22][23].…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, while the patterns of care provide insights into how end users are applying this technology in the real world, we are limited by the lack of outcomes data directly tied to this dataset and the identified trends in UHfx and adaptive therapy usage. However, reports on clinical outcomes for MRIdian with or without adaptive therapy in both prospective and retrospective series continue to grow [13] , [39] , [40] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , and completed and ongoing prospective trials will provide additional insights. (NCT03621644, NCT04331041, NCT04247165, NCT04162665, NCT04242342, NCT04020276, NCT04915508, NCT04384770, NCT04402151, NCT04422132, NCT03541850, NCT03916419, NCT03936478, NCT03612648, NCT03878485, NCT03972072, NCT04376502, NCT04115254, NCT04368702).…”
Section: Discussionmentioning
confidence: 99%
“…Weykamp et al [ 54 ], using the 0.3 T system for MR-Linac for hepatocellular carcinoma, showed that 5-fraction hypofractionation was well-tolerable with minimum toxicity with 2 years of overall survival of 82%, which is an impressive outcome. For oligometastatic cases arising from breast cancer, Tan et al [ 55 ] showed better outcomes with minimal toxicity, as reported by the patients.…”
Section: Successmentioning
confidence: 99%